1995
DOI: 10.1080/00380768.1995.10419560
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate transport pathway into soybean nodules traced by tungstate and15NO3-

Abstract: Tungstate (WO42-) was used as an anion tracer in soybean plants, and the distribution of tungsten (W) in roots and nodules was examined by electron probe X-ray microanalysis (EPMA) and chemical analysis. At 3 d after treatment with 1 mM tungstate, a large amount of W accumulated in root cortex, while the movement of W into the nodules was limited. It is suggested that external anions cannot be readily transported into the nodule cortical region via the apoplasm. In contrast, after treatment with 1.7 mM 1~NO3-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…This agrees with findings of Mizukoshi et al (1995) who observed that after a 3 days treatment of soybean plants most of the tungsten taken up is deposited in the root cortex. Taking that in mind one should expect the most distinct tungsten effects in the roots.…”
Section: Discussionsupporting
confidence: 94%
“…This agrees with findings of Mizukoshi et al (1995) who observed that after a 3 days treatment of soybean plants most of the tungsten taken up is deposited in the root cortex. Taking that in mind one should expect the most distinct tungsten effects in the roots.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, it seems more likely that a catabolic product of ureide resulting from the high concentrations of ureides in the shoot (Table I) might be more closely associated with the triggering mechanism for the observed feedback response. Such a conclusion is consistent with the suggestion of Mizukoshi et al (1995) and Bacanamwo and Harper (1997) that Asn might be closely linked to a feedback inhibition of nitrogenase activity. The possibility of a shoot-derived signal on nitrogenase activity has also been indicated in other experiments.…”
Section: Discussionsupporting
confidence: 80%
“…Neo and Layzell (1997) suggested that Gln was the most likely candidate for the feedback signal compound. However, nitrate inhibition studies with soybean implicated changes in Asn concentration in the regulation of N 2 -fixation activity (Mizukoshi et al, 1995;Bacanamwo and Harper, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nodule growth and N 2 fixation activity were suppressed only in the nodules formed on the roots treated with nitrate. This might be due to a high accumulation of nitrate in those roots and nodules [24], especially in a cortical part [25]. In contrast to local regulation, some studies have revealed that nitrate systemically controls nodulation and N 2 fixation under the presence of a high concentration of nitrate [26] or the continuous supply of low concentration (1 mM) of nitrate [24].…”
Section: Introductionmentioning
confidence: 99%